Cyclic Structure of the Lower-Middle Jurassic Sediments of the East Manych Trough and the Prikum Uplift System of the East Pre-caucasus Region - M. E. Voronin; A. N. Stafeev; V. Yu. Bliznyukov; R. S. Sautkin; A. V. Mordasova; R. M. Gilaev (Georesursy, 2025)
The paper presents the results of the analysis of the structure and composition of the terrigenous complex of the Lower-Middle Jurassic sediments of the East Manych Trough and the Prikum uplift system. The structure of the Lower Jurassic rocks is clarified and it is shown that the area of their distribution is associated with the troughs and depressions of the pre-Jurassic paleorelief. The Middle Jurassic sediments are more widespread and their thicknesses gradually increase in the northeastern direction. The Lower-Middle Jurassic sediments are productive, but new discoveries have not been made for more than 20 years, which requires new geological and methodological approaches. Currently, one of the wellknown and effective approaches to dissection and delineation of regionally traceable single-age reservoir rocks in “dumb” complexly built terrigenous strata is cyclostratigraphic analysis. Four transgressive-regressive sedimentary cyclites were identified in the Lower-Middle Jurassic sediments. The transgressive parts of the cyclites are confined to silty-clayey rocks of predominantly marine genesis, while the regressive parts are confined to silty-sandy rocks of coastal-marine and continental genesis. The boundaries of cyclites are tied to seismic sections, which allowed us to trace the distribution of cyclites in the area and construct maps of thicknesses of each cyclite. All discovered fields in the East Pre-caucasus are located in regressive parts of the cyclite. All discovered fields in the East Pre-caucasus are located in regressive parts of the cyclite. The Lower Jurassic reservoirs are confined to river channels, while the Middle Jurassic reservoirs are mainly associated with shallow-marine sediments of deltaic genesis.